Development of multi-criteria group decision making for supplier selection in Malaysian Industrialised Building System (IBS) - Mazri, Yaakob (2023)
Supplier selection is a very important activity in construction supply chain, especially in Industrialised Building System (IBS) where most building components are not produced at the construction site. There is a need for accurate decisions in selecting suppliers, because inaccurate selection can cause serious construction problems such as project delays and cost overruns. With the availability of varied criteria and many suppliers, the process of selecting suppliers for specific project needs becomes more difficult. Until now, a systematic approach to selecting the correct IBS supplier is largely neglected in the literature. This highlights the need for aided decision making tool for correct supplier selection by using a decision support system (DSS). This research aimed to develop a DSS, namely myib3s, to resolve the identified issues. Specifically, the research objectives are to identify criteria for selecting IBS supplier, next is to develop multi-criteria DSS for IBS supplier selection, then to evaluate the utility and usability of the developed DSS. It was developed by integrating user interface and supplier database, with the fuzzy Technique for Order of Preference by Similarity to Ideal Solution (fuzzy TOPSIS) model, using the .NET platform. Data from two IBS construction projects in Malaysia were used for validation and demonstrated the usability of the developed DSS. The findings indicated a comparable result of myib3s with current practice. In addition, it also presented a new framework for next-generation-DSS using .NET platform. By leveraging latest technology, the DSS produced in this study is applicable to any Multi-Criteria Decision Making (MCDM) or related mathematical modelling technique. In the practical sense, this DSS can also be used as a guideline for practitioners towards the betterment of IBS supplier selection by introducing an innovative decision making approach that can minimise time, risk, and also lead to effective management of IBS projects.